Burden of Topical Treatments in Psoriasis and Preferred Criteria of Choice: A Survey-Based Evaluation of Patients in Europe - Anthony Bewley; Lauren Hiribarne; Jordi Galván; Sicily Mburu (Adis, Springer Healthcare, 2024)
Abstract Introduction Topical treatments (TT) are widely used in psoriasis management. While psoriasis itself has been associated with diminished quality of life and mental well-being, the impact of TT remains underexplored. This study aimed to evaluate the burden of TT on the daily lives of patients with psoriasis, the convenience of the TT, and the choice criteria. Methods Patients were recruited across five countries (France, Germany, Italy, Spain, UK) by Wefight and the International Federation of Psoriasis Associations (IFPA) to complete a 29-item online survey. Results A total of 766 patients completed the survey (54% female, mean age of 53 years). The mean body surface area covered by psoriasis was 7%, predominantly on the scalp and elbows. Participants had been living with psoriasis for a mean duration of 18 years. Of the respondents, 34% reported feeling affected by their TT in their daily routines and activities. Those feeling affected were more likely to have a more complex disease, be using more treatments, or be diagnosed more recently compared to those less affected. Among those most affected by their TT, 27% reported a strong impact on mental health, 30% on sexual life, and 25% on physical activities, compared to 7%, 6% and 4% in those least affected, respectively. Both cohorts considered tolerability factors such as "does not cause itching/burning" and "good tolerability" as most important when choosing a topical. However, only least affected participants regarded convenience factors such as "does not run off," "ease of application," "does not leave stains" among others equally as important. Conclusion Overall, one-third of patients report a significant burden of TT on their daily lives. These patients have different criteria of choice, highlighting the importance of communication between physicians and patients to tailor treatment to individual preferences, thereby enhancing adherence and treatment outcomes.